Patient safety and patients’ fall risk in the pre-hospital phase of emergency medical services - Mikos, Marcin; Żurowska-Wolak, Magdalena; Paradowska, Zofia; Czerw, Aleksandra Izabela (Journal of Education, Health and Sport, 2019)
In Poland, falls constitute the major cause of hospitalisation and deaths among all types of accidents. Around 5,000 people die because of that per year (the standardised rate: 8.8. per 100,000 population). Nearly 70 % of the deaths caused by falls are related to slips and trips. A total of 11.3% deaths are connected with falling down stairs and other inclined surfaces. As many as 34 % of fatal falls remain further unexplained.